2005
DOI: 10.1159/000088171
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gender Differences in Ischemic and Nephrotoxic Acute Renal Failure

Abstract: Background/Aims:Recent work has shown that female animals are more resistant to ischemic acute renal failure (ARF) than male animals. The mechanism underlying the gender difference is unclear. Moreover, whether the gender difference holds true for ARF induced by other insults is unknown. This study sought to determine the gender differences in ischemic and nephrotoxic ARF. Methods: Gender differences were tested in two experimental models of ARF. For ischemic ARF, bilateral clamping of renal pedicles was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 37 publications
2
83
1
Order By: Relevance
“…In C57 mice, one dose of cisplatin induced acute renal failure within a few days (data not shown; Wei et al, 2005). Renal tissues were collected to determine PUMA-a by immunoblot analysis.…”
Section: Resultsmentioning
confidence: 95%
“…In C57 mice, one dose of cisplatin induced acute renal failure within a few days (data not shown; Wei et al, 2005). Renal tissues were collected to determine PUMA-a by immunoblot analysis.…”
Section: Resultsmentioning
confidence: 95%
“…The kidneys of males are much more susceptible to IRI than those of females. Although gender differences in kidney IRI susceptibility have been characterized in rats (Fekete et al 2004) and mice (Park et al 2004;Wei et al 2005), mechanistically, very limited information is available for the gender differences in kidney IRI. Szabo and colleagues suggested that estrogen might play an important role in protecting females from ischemic ARF by limiting endothelin activation (Müller et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…3 Despite of the comprehensive alien about cellular and molecular mechanisms of cell injury, it has been considered that necrosis and apoptosis of renal epithelial cells are the upshot of acute renal failure. 26 It has been endorsed that newly identified kidney marker kidney injury molecule-1 (KIM-1) which is customary in urine for an extended phase, nonetheless, can be distinguished in the kidney and urine in numerous animal models of nephrotoxins. 27 During ischemia reperfusion, mitochondria accuses permeability evolution, prompted by assorted circumstances, such as amplified outset of reactive oxygen species (ROS), diminution of antioxidants, modification of pyridine nucleotide fractions, fluctuation of Ca 2+ concentration, and engorge of inorganic phosphate in the prevailing surroundings.…”
Section: Introductionmentioning
confidence: 99%